1988
DOI: 10.1093/oxfordjournals.humrep.a136796
|View full text |Cite
|
Sign up to set email alerts
|

The effect of age on the cyclical patterns of plasma LH, FSH, oestradiol and progesterone in women with regular menstrual cycles

Abstract: Luteinizing hormone (LH), follicle-stimulating hormone (FSH), oestradiol and progesterone concentrations in plasma were obtained daily throughout the menstrual cycles of 94 regularly cycling women, aged between 24 and 50 years. Although mean LH concentrations changed little with advancing age, mean FSH concentrations were significantly (P less than 0.001) elevated from the age of 39 years. FSH concentrations in the oldest women studied (48-50 years) were approximately 3-fold greater than in the younger control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
93
1
5

Year Published

1997
1997
2016
2016

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 218 publications
(104 citation statements)
references
References 7 publications
5
93
1
5
Order By: Relevance
“…Current evidence suggests that the estradiol level decreases relatively late in the process of ovarian aging and that the plasma level of progesterone does not change significantly (42)(43)(44). The current results indicated that the plasma levels of estradiol and progesterone decreased in the Mod group of mice.…”
Section: Discussionmentioning
confidence: 46%
“…Current evidence suggests that the estradiol level decreases relatively late in the process of ovarian aging and that the plasma level of progesterone does not change significantly (42)(43)(44). The current results indicated that the plasma levels of estradiol and progesterone decreased in the Mod group of mice.…”
Section: Discussionmentioning
confidence: 46%
“…During this period, women still have normal regular menstrual cycles and there are no clinical signs or symptoms of perimenopause [71][72][73][74][75].…”
Section: Menopausementioning
confidence: 99%
“…Despite the presence of a normal day 3 FSH, some patients respond poorly to controlled ovarian hyperstimulation. Serum FSH levels increase early in reproductive ageing and a rise in luteinizing hormone (LH) levels is observed at a later stage [6]. As a result, an exaggerated day 3 FSH/LH ratio even with normal basal FSH has been reported to be a sign of Capsule An elevated basal FSH/LH ratio in the presence of a normal basal FSH level is associated with poor IVF outcome in older women but not in young women.…”
Section: Introductionmentioning
confidence: 99%